2003
DOI: 10.1152/ajplung.00260.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of eosinophils leads to a reduction of allergen-induced pulmonary pathology

Abstract: A strategy to deplete eosinophils from the lungs of ovalbumin (OVA)-sensitized/challenged mice was developed using antibody-mediated depletion. Concurrent administration [viz. the peritoneal cavity (systemic) and as an aerosol to the lung (local)] of a rat anti-mouse CCR3 monoclonal antibody resulted in the abolition of eosinophils from the lung such that the airway lumen was essentially devoid of eosinophils. Moreover, perivascular/peribronchial eosinophil numbers were reduced to levels indistinguishable from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
59
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 36 publications
6
59
0
Order By: Relevance
“…In our chronic model of allergic airway disease, we observed impaired allergen-induced recruitment of eosinophils, macrophages, and lymphocytes. Our data showing that murine CCR3 is predominantly expressed by eosinophils are consistent with previous studies (19,20). These observations suggest that leukocyte recruitment in chronic allergic inflammation is orchestrated, at least in part, via CCR3 signaling in eosinophils, although we cannot exclude signal transduction events in other cells such as basophils and epithelial cells, because they have been shown to express low levels of CCR3 at least in the human system (21,22).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our chronic model of allergic airway disease, we observed impaired allergen-induced recruitment of eosinophils, macrophages, and lymphocytes. Our data showing that murine CCR3 is predominantly expressed by eosinophils are consistent with previous studies (19,20). These observations suggest that leukocyte recruitment in chronic allergic inflammation is orchestrated, at least in part, via CCR3 signaling in eosinophils, although we cannot exclude signal transduction events in other cells such as basophils and epithelial cells, because they have been shown to express low levels of CCR3 at least in the human system (21,22).…”
Section: Discussionsupporting
confidence: 91%
“…To define a causative relationship between the recruitment of eosinophils and the onset or progression of pulmonary pathologies associated with allergic asthma, multiple experimental approaches have been used to deplete animals of eosinophils, including manipulation of cytokine (e.g., IL-5 and eotaxins) levels via gene targeting and neutralizing antibodies and depletion of eosinophils using an anti-CCR3 antibody (19,20,(33)(34)(35). More recently, Lee et al (6) targeted the depletion of eosinophils (these mice are designated as PHIL) using an eosinophil-specific promoter to drive expression of a cytocidal protein, diphtheria toxin A.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy has been successfully used using anti-CCR3 treatment and in CCR3 Ϫ/Ϫ mice, reducing eosinophilia and the corresponding airway hyperreactivity. 28,29 It may be that different CCR3 ligands are important for various stages of eosinophil migration and/or activation within the airway. Interestingly, the anti-CCL28-treated animals had reduced peribronchial eosinophil accumulation but we could neither find significant evidence of reduced airway eosinophil accumulation nor reduced activation parameters (LTC 4 ) within BAL fluid samples.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In the mouse system, CCR3 expression is almost exclusively detected on eosinophils. 22,23 Importantly, recent studies have demonstrated that CCR3 disruption impaired eosin-ophil recruitment in acute models of experimental asthma. 24 -26 In addition to regulating eosinophil trafficking into mucosal tissues, the eotaxins activate the respiratory burst apparatus, induce degranulation, and up-regulate adhesion molecule expression.…”
mentioning
confidence: 99%